2012
DOI: 10.1155/2012/843048
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling Study of Yang Deficiency Syndrome in Hepatocellular Carcinoma byH1NMR and Pattern Recognition

Abstract: This study proposes a 1H NMR-based metabonomic approach to explore the biochemical characteristics of Yang deficiency syndrome in hepatocellular carcinoma (HCC) based on serum metabolic profiling. Serum samples from 21 cases of Yang deficiency syndrome HCC patients (YDS-HCC) and 21 cases of non-Yang deficiency syndrome HCC patients (NYDS-HCC) were analyzed using 1H NMR spectroscopy and partial least squares discriminant analysis (PLS-DA) was applied to visualize the variation patterns in metabolic profiling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Mitochondrial toxicity, commonly observed in HAART, might be responsible for hepatotoxicity and nephrotoxicity [ 34 ]. Mitochondrial dynamics indeed plays a key role in energy conversion and metabolism, cell life and death, and disease [ 35 ], and various aspects of metabolism, including lipid, amino acid, and energy metabolism, were imbalanced or weakened in Yang deficiency syndrome patients [ 36 ]. Whether Yang-Deficient Consitution is susceptible to mitochondrial toxicity is worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial toxicity, commonly observed in HAART, might be responsible for hepatotoxicity and nephrotoxicity [ 34 ]. Mitochondrial dynamics indeed plays a key role in energy conversion and metabolism, cell life and death, and disease [ 35 ], and various aspects of metabolism, including lipid, amino acid, and energy metabolism, were imbalanced or weakened in Yang deficiency syndrome patients [ 36 ]. Whether Yang-Deficient Consitution is susceptible to mitochondrial toxicity is worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic causes of YDCS are in accordance with the record of the ancient Chinese medicine classic Nei jing , which said that too much cold herb intake is harmful to Yang. The basic process of YDCS development is as follows: take too much cold herb, hurt the body righteousness, and result in damage of lung, spleen, kidney, liver, and other organs, poor circulation of blood, fatigue, chills, laziness, long-time lying, lack of movement, reduced water intake, loose stools, and other symptoms [ 2 ]. It can be divided into two major categories: Yang-deficiency (YD) constitution and the YDCS stage due to the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The next important carbohydrate pathways are the glucose-alanine pathway and glycolysis which were marked by D-glucose and NADP and D-glucose and fructose-6-phosphate, respectively. As mentioned above, bioenergetics of cancer cells have shown that glucose is the main energy source for body cells and tumor cells consume a high level of glucose [ 39 ]. Changing glucose metabolism is one of the hallmarks of cancer.…”
Section: Discussionmentioning
confidence: 99%